Handbook of real estate and macroeconomics: An introduction - Charles Ka Yui Leung (Osaka University, Institute of Social and Economic Research (ISER), 2021)
This paper provides some background for the book, Handbook of Real Estate and Macroeconomics. It gives an overview of different chapters and how various themes and ideas can be connected. Directions for future research are also discussed.
Keywords: E00; G00; R00; 330; housing; macroeconomics; real estate; urban and regional economics